2016
DOI: 10.1080/17518423.2016.1212946
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a group circuit progressive resistance training program compared with a treadmill training program for adolescents with cerebral palsy

Abstract: Both programs were effective in improving motor function in adolescents with cerebral palsy. The GT program had generally greater benefits based on the functional measures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
38
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(41 citation statements)
references
References 41 publications
1
38
0
1
Order By: Relevance
“…Effect sizes for all studies are shown in Figure . The MCID for increase in walking speed (0.1m/s), was achieved after intervention in 12 studies . Level IV and V studies supported this positive effect of increase in walking speed as a result of gait training.…”
Section: Resultsmentioning
confidence: 92%
See 4 more Smart Citations
“…Effect sizes for all studies are shown in Figure . The MCID for increase in walking speed (0.1m/s), was achieved after intervention in 12 studies . Level IV and V studies supported this positive effect of increase in walking speed as a result of gait training.…”
Section: Resultsmentioning
confidence: 92%
“…One further study reported no change after a brief period of gait training with added ankle load . Persisting positive effects were noted in studies with follow‐up measurements from 1 month up to 6 months after cessation of intervention; however, one study was contrary to this trend, showing a decline in walking speed at 14 weeks follow‐up after resuming normal activities …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations